If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3m + 5) = -2(m + 5) Reorder the terms: -4(5 + 3m) = -2(m + 5) (5 * -4 + 3m * -4) = -2(m + 5) (-20 + -12m) = -2(m + 5) Reorder the terms: -20 + -12m = -2(5 + m) -20 + -12m = (5 * -2 + m * -2) -20 + -12m = (-10 + -2m) Solving -20 + -12m = -10 + -2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2m' to each side of the equation. -20 + -12m + 2m = -10 + -2m + 2m Combine like terms: -12m + 2m = -10m -20 + -10m = -10 + -2m + 2m Combine like terms: -2m + 2m = 0 -20 + -10m = -10 + 0 -20 + -10m = -10 Add '20' to each side of the equation. -20 + 20 + -10m = -10 + 20 Combine like terms: -20 + 20 = 0 0 + -10m = -10 + 20 -10m = -10 + 20 Combine like terms: -10 + 20 = 10 -10m = 10 Divide each side by '-10'. m = -1 Simplifying m = -1
| 3x+14+6x+5+80=180 | | 36k=41.5k | | 5x^2-x-9=2x^2+2x | | 12x-9+24x+4=43 | | 4x-9x=4 | | Q+4/24=11/4 | | 5v-18-4v=-36 | | 7+n=7 | | 5(2x+3)=10x+10 | | 8x-24=6x+4 | | 8x^3-x^2-72x-9=0 | | nover-1.5=-1.2 | | x-4/4+x=0 | | 13=2x+5(-2x+17) | | 150p-105+13p=58 | | l+4=16 | | -30=-3+1y | | 13x+72=-23x | | (4ab)(4ab)(4ab)= | | 4x^2+6x+2=90000 | | 3c+5+c=-6+4c+8 | | 16=7+n | | 17+-9y=-3+7y | | 6n=243 | | 8cos^2(x)-2=0 | | 15/-2h=15/12 | | 14+x=6 | | 4b^2-28b-120=0 | | 5c^2=35c | | x=4-5(6) | | x^3=93 | | 6-3v=3v-18 |